Penanaman kreativitas di ekstrakurikuler science club SD Muhammadiyah Pakel program plus - Panji Hidayat; Ida Megawati (Universitas Sarjanawiyata Tamansiswa, 2023)
Facing the 21st century, Indonesia needs human resources who have the creativity and skills to produce output in the form of innovative work. Therefore, school programs are needed to facilitate students in learning with creative skills to become problem solvers in the future. Against this background, this study aims to describe aspects, strategies, and supporting and inhibiting factors in fostering creativity through science extracurriculars at SD Muhammadiyah Pakel Program Plus. This research is categorized as qualitative descriptive research. The main focus of this research is the implementation of the extracurricular Science Club in instilling creativity in elementary school students. Data collection was carried out by observation techniques, interviews, and documentation. The research subjects were the principal, 2 science extracurricular teachers, and 6 students. Data validity is carried out through a triangulation process, both techniques and sources. Data analysis used Miles and Huberman's inductive interactive data model. The results showed that the inculcation of creativity through science extracurriculars at SD Muhammadiyah Pakel Program Plus was seen from 1) Aspects of creativity instilled, namely (1) Cognitive (talent) in the form of fluent, flexible, original, and detailed thinking. Skills. (2) Affective (non-aptitude) in the form of curiosity and being challenged. 2) Strategy to foster creativity with 4 stages, namely personal, process, driver, and product. 3) The supporting factors are mental stimulus, environmental conditions, and the role of the teacher. The inhibiting factors are evaluation, reward, and competition.